ACM Member News: INNOVATIONS IN ALGORITHMS FOR TENSOR DECOMPOSITIONS. - Delaney, John (Communications of the ACM, 2021)
The article briefly profiles Association for Computing Machinery (ACM) member and Sandia National Laboratories technical staff member Tamara Kolda, particularly her work with algorithms as related to tensor decompositions.